Employee Satisfaction and Retention in the Banking Sector of Bharatpur Metropolis in Nepal: A Confirmatory Factor Analysis - Subedi, Indra Raj; Kafle, Sarad Chandra; Kushwaha, Satyendra; Khanal, Babu Ram (OCEM Journal of Management, Technology & Social Sciences, 2024)
Bharatpur, often referred to as the “alternative capital city” of Nepal, boasts a compact urban landscape with a notable presence of banks, earning it the name “Bank City” in recent years. Bharatpur Metropolitan City is situated in the Bagmati Province and is one of six metropolitan in Nepal. Bharatpur’s strategic central location is of national significance. The increasing phenomenon of brain drain, a prominent concern in Nepal, has been affecting employee satisfaction and retention, and its impact is keenly observed in Bharatpur. In this context, the primary objective of this study is to find out the level of satisfaction and retention of employees working in commercial banks in Bharatpur Metropolitan City, Chitwan, Nepal. A structured questionnaire will be used to collect primary data to accomplish this objective. A total of one hundred fifty-six employees from both government and private banks, spanning all hierarchical levels, which were randomly selected through a comprehensive field survey. Confirmatory Factor Analysis is employed to validate employee satisfaction and retention factors in banking industries. The empirical findings from the data analysis revealed a moderate level of employee satisfaction and retention in the study area. This research not only contributes to the academic community, offering insights into the application of Confirmatory Factor Analysis in various research studies, but also holds practical value for corporate and government banking authorities. It sheds light on areas where improvements can be made to enhance employee satisfaction and retention, ultimately fostering a more robust and sustainable workforce in the financial sector.